Green advertising and its impact on environmentally friendly consumption choices - A review - Krstić, Jelena; Kostić-Stanković, Milica; Cvijović, Jelena (Industrija, 2021)
Research on various environmental topics, among which is the topic of green advertising, has been growing during last three decades, but it is yet to gain its full potential. Since the topic of green advertising has been gaining rising attention of scholars, the body of knowledge on this topic has been growing as well. Green advertising in general aims to promote products produced in an environmentally-friendly manner, or to promote advertiser’s corporate responsibility toward an environment. The evaluation of green advertising effectiveness is necessary in order to stimulate cognitive and affective reactions of consumers to green advertisements, as well as their subsequent environmentally friendly behaviour. This article contains the review of the relevant literature on the topic of green advertising effectiveness. The findings of the literature review indicate that green advertising represents an effective communication means to influence consumers’ attitudes and behaviour, even though its effectiveness is often mediated by certain factors, like: consumers’ environmental consciousness, consumers’ regulatory focus, consumers’ scepticism, claim type.